Sacred Symbolism in Ziyarat Warith: An Analytical Study of Three English Translations (Journal of the College of Education for Women, 2025)
Ziyarat Warith (ZW) is rightly considered a landmark in the Islamic legacy; however, it has not yet received its deserved attention in translation into English. Attempting to fill a gap in the literature, the present study examines how sacred symbolism in ZW is translated into English. Based on Tillich’s (2009) premise that symbols are an integral part of religious language, the inclusion of sacred symbolism in ZW is not accidental. Rather, it represents the archetype reflecting the Infallible Imam’s status. Therefore, it poses serious challenges for translators because of its deep connotations. This study aspires to achieve a twofold objective; firstly, to highlight the significance of sacred symbols in ZW according to Perrine's (1992), secondly, to detect how these symbols have been transferred into English. For the purposes of the study, three different translations by Ansariyan (2005), Kazmi (2014) and Qarai (2019) are examined in terms of the adopted translation strategies. Five selected extracts from ZW represent the data of study. It is hypothesized that translators will use explicitation to further clarify the original text. Qualitative analysis of the data revealed that sacred symbolism is mostly lost in translation when translators literally approached ZW. It is concluded that the complex nature of sacred symbolism demands being engaged with Shiite interpretation and exegesis to make the proper choice of translation strategy.